Hours of work and time use of employed people in Estonia and Finland - Aedna, Elmar; Romppanen, Antti (VATT-keskustelualoitteita = VATT-discussion papers, ISSN 0788-5016, 1992)
Abstract (1 s.). - Tiivistelmä (1 s.).
Keywords: työaika : Suomi; työaika : Viro; vuosiloma : Suomi; vuosiloma : Viro